Ligustilide suppresses RANKL‐induced osteoclastogenesis and bone resorption via inhibition of RANK expression. Issue 11 (22nd August 2019) - Wang, Dairong; Li, Jia; Feng, Wenyu; Yao, Jun; Ou, Luanhai; Liao, Shijie; Liu, Yun; Li, Boxiang; Lin, Chengsen; Zhao, Jinmin; Zhao, Guoping
Abstract: Osteoclast (OC) is the only cell involved in bone resorption. Dysfunction of OCs leads to a variety of bone diseases. Ligustilide (LIG) is the main component of the volatile oil isolated and purified from Angelica sinensis . LIG exerts many pharmacological activities, but its effects on osteoclastogenesis and bone resorption are still unclear. Our study showed that LIG inhibited receptor activator of nuclear factor‐κB (NF‐κB) ligand‐induced OC formation and activation in a dose‐dependent manner. Additionally, LIG downregulated the messenger RNA (mRNA) expression of OC‐specific genes, such as V‐ATPase d2, tartrate‐resistant acid phosphatase, a dendritic cell‐specific transmembrane protein, cathepsin K, and nuclear factor of activated T cells cl. Furthermore, LIG blocked the activation of NF‐κB/extracellular signal‐regulated kinase/p38/immunoreceptor tyrosine‐based activation motif signaling pathways. Crucially, the expression of tumor necrosis factor receptor‐associated factor 6 proteins and the expression of receptor activator of NF‐κB mRNA were inhibited by LIG. However, LIG did not affect the formation and mineralization of osteoblasts. Collectively, this observation suggests that LIG may serve as a promising agent for the prevention and treatment of diseases caused by abnormal bone resorption. Abstract : This is a valuable study. Ligustilide suppresses receptor activator of nuclear factor‐κB ligand (RANKL)‐induced osteoclastogenesis and bone resorption via inhibition of RANK expression.